Reaction Mechanism and Substrate Specificity of Iso-orotate Decarboxylase: A Combined Theoretical and Experimental Study - Sheng, Xiang; Plasch, Katharina; Payer, Stefan E.; Ertl, Claudia; Hofer, Gerhard; Keller, Walter; Braeuer, Simone; Goessler, Walter; Glueck, Silvia M.; Himo, Fahmi; Faber, Kurt (Frontiers in Chemistry, 2018)
The C-C bond cleavage catalyzed by metal-dependent iso-orotate decarboxylase (IDCase) from the thymidine salvage pathway is of interest for the elucidation of a (hypothetical) DNA demethylation pathway. IDCase appears also as a promising candidate for the synthetic regioselective carboxylation of N-heteroaromatics. Herein, we report a joint experimental-theoretical study to gain insights into the metal identity, reaction mechanism and substrate specificity of IDCase. In contrast to previous assumptions, the enzyme is demonstrated by ICPMS/MS measurements to contain a catalytically relevant Mn2+ rather than Zn2+. Quantum chemical calculations revealed that decarboxylation of the natural substrate (5-carboxyuracil) proceeds via a (reverse) electrophilic aromatic substitution with formation of CO2. The occurrence of previously proposed tetrahedral carboxylate intermediates with concomitant formation of HCO3− could be ruled out on the basis of prohibitively high energy barriers. In contrast to related o-benzoic acid decarboxylases, such as γ-resorcylate decarboxylase and 5-carboxyvanillate decarboxylase, which exhibit a relaxed substrate tolerance for phenolic acids, IDCase shows high substrate fidelity. Structural and energy comparisons suggest that this is caused by a unique hydrogen bonding of the heterocyclic natural substrate (5-carboxyuracil) to the surrounding residues. Analysis of calculated energies also shows that the reverse carboxylation of uracil is impeded by a strongly disfavored uphill reaction.